Challenges in Teaching English at the University Level: Guidance and Self-reflection for English Language Instructors - Adolfina M. S. Moybeka; Astina Y Kabbi (Universitas Muhammadiyah Enrekang, 2024)
English language learning in higher education is a topic that continues to receive attention, especially in the context of globalization and the importance of cross-cultural communication. This paper outlines the main issues faced by English as a foreign language’ students, covering challenges in instruction as well as the need for reflection for teachers. The main problems in English language instruction in higher education include the varying ability levels of students, irrelevant curriculum, and the suboptimal use of technology in teaching. English teachers also often face difficulties in assessing student progress and developing effective teaching strategies. Reflection is a key element in overcoming these problems. English teachers need to regularly reflect on their teaching practices, identify their weaknesses and strengths, and adapt teaching methods according to students' needs. In addition, cooperation between English teachers and universities in the development of relevant curricula and continuous teacher training are also important in addressing the problems of English language learning. This paper further discusses the problems of English language instruction in higher education, provides practical suggestions for English lecturers and students, and emphasizes the importance of reflection and collaboration in improving the quality of English language learning at the higher education level